KESIAPAN SISWA TEKNIK GAMBAR BANGUNAN SMK NEGERI 2 PAYAKUMBUH SEBELUM PRAKTEK KERJA INDUSTRI - 348-355 , Wahyu Hutria (CIVED, 2014)
ABSTRACT   Base on the prasurvey, the students readiness of Industrial Work Practice were less of knowledge, attitude and skill domain. The research aim was to know the degree of student of XIth of Teknik Gambar Bangunan of SMK Negeri 2 Payakumbuh on the Industrial Work Practice during 2013/2014 periode. This research use the descriptive method. The research subject were the students of XIth of Teknik Gambar Bangunan who will join the Industrial Work Practice activities. The data collecting conducted by using the observation sheet, which were used descriptive analysis qualitative technique. The result of this research indicate that the students of XIth of Teknik Gambar Bangunan of SMK Negeri 2 Payakumbuh in knowledge and attitude domain were in the ready categorize of Industrial Work Pactice. While the skill domain were devide of two part which were ready and ready categorize. Key word : Readiness, Industrial Work Practice, Knowledge, Attitude, Skill.